2012
DOI: 10.1037/a0026730
|View full text |Cite
|
Sign up to set email alerts
|

Tagging multiple emotional stimuli: Negative valence has little benefit.

Abstract: Six experiments examined the influence of emotional valence on the tagging and enumeration of multiple targets. Experiments 1, 5 and 6 found that there was no difference in the efficiency of tagging/enumerating multiple negative or positive stimuli. Experiment 2 showed that, when neutral-expression face distractors were present, enumerating negative targets was faster overall, but was only more efficient for small numbers of targets. Experiments 3 and 4 determined that this negative target advantage was most l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
21
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 93 publications
(243 reference statements)
0
21
2
Order By: Relevance
“…Experimental manipulations that have an effect on attention also influence performance in enumeration tasks (Trick & Pylyshyn, 1994). However, although the effects of emotion on attention have been demonstrated in many tasks, Watson and Blagrove (2012) found that their manipulations neither sped enumeration (as would be predicted by attentional capture) nor delayed it (as would be expected if emotional factors made it difficult to disengage attention). To determine whether this surprising result would recur in other enumeration tasks, we investigated the impact of valence (the negativity or positivity of the emotion) and arousal (how exciting or stimulating the emotion is) on a subsequent enumeration task where participants were required to determine the number of dots with accuracy.…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…Experimental manipulations that have an effect on attention also influence performance in enumeration tasks (Trick & Pylyshyn, 1994). However, although the effects of emotion on attention have been demonstrated in many tasks, Watson and Blagrove (2012) found that their manipulations neither sped enumeration (as would be predicted by attentional capture) nor delayed it (as would be expected if emotional factors made it difficult to disengage attention). To determine whether this surprising result would recur in other enumeration tasks, we investigated the impact of valence (the negativity or positivity of the emotion) and arousal (how exciting or stimulating the emotion is) on a subsequent enumeration task where participants were required to determine the number of dots with accuracy.…”
mentioning
confidence: 85%
“…In their study, Watson and Blagrove (2012) found that valence had no effect on RT or RT slopes in simple enumeration. Subitising and counting emerged as usual, as shown by differences in RT slopes between 1 to 3 and 5 to 8 of items, but there was no effect of emotional valence—even when participants were forced to decide whether the faces were positive, negative, or neutral at the end of each trial (Experiments 5 and 6).…”
mentioning
confidence: 92%
See 3 more Smart Citations